“Fertirriego a base de tres (3) dosis de humus de lombriz en el cultivo organopónico del del tomate (lycopersicom esculentum L.)” - Campos Pérez, Jorge Luis (2008)
The present work, 1 am made of the 2 of February until the 30 of May of the 2007. 1 settle in the roof of the house of Mr. Juan Carlos Perez Cubas, located in Jr. San Pedro Nº 360 (started off high) district of Tarapoto, province of San Martin. The objective was to evaluate the effect of the doses of humus of lombriz, applied in salid form (witness), and three doses of humus in solutions (fertrriego); in the tomate culture variety Grande River under the organpónico system. Use the design completely at random, with 04 treatments and 03 repetitions; for the implementation of this design a adjustment became of a wood structure, and the plants were seeded in individual flowerpots. lt was used a sterile substrate (rice husk), this far the treatments applied like fertirriego, and 1,0 kg/flowerpot of humus of lombriz (witness). For the treatments applied in fertirriego a solution was prepared mother, of the following form; 1 am diluted a kilogram of humus of lombriz by each two liter of distilled water, next 1 let myself settle by space of 12 hours, later took shelter the part eliminates in another container. The treatments that 1 am used, were three proportions of volume of solution mother on distilled vol u me of water (T1 = Proportion 1: 1, T2= Proportion 1 :2 and T3= 1 :3 Proportion). The results determined, that the treatment witness, obtained the best yield (269 TN/ha.) and 1 turn out to be most profitable, since with a smaller production cost 1 generate a great utility.